Nanoengineered drug-releasing Ti wires as an alternative for local delivery of chemotherapeutics in the brain - Gulati, Karan (Dove Medical Press, 2012)
The blood–brain barrier (BBB) blocks the passage of active molecules from the blood which makes drug delivery to the brain a challenging problem. Oral drug delivery using chemically modified drugs to enhance their transport properties or remove the blocking of drug transport across the BBB is explored as a common approach to address these problems, but with limited success. Local delivery of drugs directly to the brain interstitium using implants such as polymeric wafers, gels, and catheters has been recognized as a promising alternative particularly for the treatment of brain cancer (glioma) and neurodegenerative disorders. The aim of this study was to introduce a new solution by engineering a drug-releasing implant for local drug delivery in the brain, based on titanium (Ti) wires with titania nanotube (TNT) arrays on their surfaces. Drug loading and drug release characteristics of this system were explored using two drugs commonly used in oral brain therapy: dopamine (DOPA), a neurotransmitter agent; and doxorubicin (DOXO), an anticancer drug. Results showed that TNT/Ti wires could provide a considerable amount of drugs (>170 μg to 1000 μg) with desirable release kinetics and controllable release time (1 to several weeks) and proved their feasibility for use as drug-releasing implants for local drug delivery in the brain.